Air Pollution Particulate Matter Collected from an Appalachian Mountaintop Mining Site Induces Microvascular Dysfunction. (15th February 2013) - Knuckles, Travis L.; Stapleton, Phoebe A.; Minarchick, Valerie C.; Esch, Laura; McCawley, Michael; Hendryx, Michael; Nurkiewicz, Timothy R.
Abstract Objective Air pollution PM is associated with cardiovascular morbidity and mortality. In Appalachia, PM from mining may represent a health burden to this sensitive population that leads the nation in cardiovascular disease, among others. Cardiovascular consequences following inhalation of PMMTM are unclear, but must be identified to establish causal effects. Methods PM was collected within 1 mile of an active MTM site in southern WV. The PM was extracted and was primarily <10 μm in diameter (PM10), consisting largely of sulfur (38%) and silica (24%). Adult male rats were IT with 300 μg PMMTM. Twenty‐four hours following exposure, rats were prepared for intravital microscopy, or isolated arteriole experiments. Results PMMTM exposure blunted endothelium‐dependent dilation in mesenteric and coronary arterioles by 26%, and 25%, respectively, as well as endothelium‐independent dilation. In vivo, PMMTM exposure inhibited endothelium‐dependent arteriolar dilation (60% reduction). α‐adrenergic receptor blockade inhibited PVNS‐induced vasoconstriction in exposed animals compared with sham. Conclusions These data suggest that PMMTM exposure impairs microvascular function in disparate microvascular beds, through alterations in NO‐mediated dilation and sympathetic nerve influences. Microvascular dysfunction may contribute to cardiovascular disease in regions with MTM sites.